The effect of posttest through “everyone is teacher here” model to biology learning outcomes - Yusnidar, Yusnidar; Putri, Nadila Aulya (JURNAL ATRIUM PENDIDIKAN BIOLOGI, 2023)
There are many problems were found in learning process of biology that effect learning outcomes become low, for instance, instructional model which are not variated. Everyone is teacher here is a type of cooperative model, it can increase students motivation and also learning outcomes. This study aims to determine the effect of pretest in everyone is teacher here model. This is an experiment with one group pretest-postest design. The study population was all second-year students at MTsN 5 Tanah Datar, and were taught by the same teacher. We used purposive sampling method. Data were analyzed with t-test. The results shows postest have average point 87,5 is higher than pretest (average point 66,8). It can concluded that the dependent variable has positive effect on learning outcomes in biology.